Exodus to the Virtual World. How Online Fun is Changing Reality : von Edward Castronova - Stingeder, Karl H. (Medienimpulse, 2011)
Verlag: Palgrave Macmillan Erscheinungsdatum: 11. November 2008 ISBN: 0230607853